THE INFLUENCE OF PERFORMANCE APPRAISAL, TRAINING, AND PLACEMENT ON PERSONNEL PERFORMANCE IN LAW ENFORCEMENT AT EAST LAMPUNG POLICE STATION - Pradnyadana, Kadek Andi; Harpain, Harpain; Barusman, Tina Miniawati (Journal of Management, Business and Social Sciences, 2024)
The purpose of this study was to determine and analyze the effect of performance appraisal, training, and placement on personnel performance in law enforcement at East Lampung Police. This study used a sample of 42 respondents who were personnel in the law enforcement section of the Criminal Investigation Unit (Satreskrim) of East Lampung Police as the object of research. The data collection method was carried out directly using questionnaires and interviews with personnel in the law enforcement section of the Criminal Investigation Unit (Satreskrim) of East Lampung Police. While the analysis used to determine the effect of independent variables (X1) performance appraisal, (X2) training, and (X3) placement on the dependent variable (Y), namely personnel performance, is multiple linear regression analysis, with the SPSS 20 program. The comes about of this consider demonstrate that employing a significant level of 0.05 since the two-sided test is 2.5% and n = 42, the t table is gotten = 2.02439.. While the t count for performance appraisal seen from the data processing output is 4.636, then for training shows a t count of 5.431, then for placement shows a thitung of 3.836 (thitung> t table) so based on this t-test, it is concluded that performance appraisal, training, and placement partially have a positive and significant effect on the performance of personnel in the law enforcement section of the Criminal Investigation Unit (Satreskrim) of East Lampung Police. With the F test, the significance level uses 0.05 (∂ = 5%), so the F table is 2.83. Meanwhile, based on the output of data processing, F count is 210.207, because F count> from F table, it can be concluded that together there is a significant influence between the independent variables (performance appraisal, training, and placement) on the dependent variable (personnel performance) in the law enforcement section of the Criminal Investigation Unit (Satreskrim) of East Lampung Police.